Light controller using PIC16F873 / Zarina Idris and Mazdiana Muhamad - Idris, Zarina; Muhamad, Mazdiana (2005)
Light controller is designed to control light in many situations. The mission of this program is to maintain and improve the quality of the light as we desired. The majority of all indoor and outdoor lighting in the home today is provided by incandescent lamps, commonly referred to as conventional "light bulbs". In this thesis, the light bulb is the most widely used lamp in residential and many commercial and industrial lighting applications for general lighting. Light controller are a type of incandescent lamp that gives "whiter" light, lasts longer, is usually small, is slightly more efficient than normal bulb. Light controller will become more popular for lighting stores, buildings, hotels, and houses. This light controller can be use at many places. For example it can be a light dimmer, light dimmer allows the knob controlling of the light output (the light intensity) of different lighting instruments. A light dimmer allows controlling of light bulb brightness. The basic idea of dimmer operation is that it limits the electrical power that gets to the light bulb. Dimmers today come in many styles to control different types of loads. There are also some other dimmer types used in some special applications (variable transformers, simple resistors for very low power bulbs and PWM controllers for DC lights). Typical light dimmer circuits use Pulse Width Modulation (PWM) to control the brightness of the bulb. It controls the brightness of the bulb by turning the bulb ON for part of time and then OFF for part of time. The brightness of the bulb is a function of the ON time to the OFF time. Dimmers designed to dim DC light bulbs generally work in this way, they just have an adjustable free-running oscillator with variable pulse width to control the light output.